Příklady uplatnění nedestruktivních geofyzikálních měření při průzkumech raně středověkých hradišť na území Přemyslovské domény i širších Čech - Křivánek, Roman (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2022)
For several decades, the Institute of Archaeology in Prague has used non-destructive geophysical methods to research fortifications. New cooperation between archaeologists and geophysicist as part of a Czech-Polish project resulted in a more systematic and targeted survey of early medieval fortifications. The results of this cooperation were presented at a workshop Use of non-destructive and destructive methods in archaeological research of early medieval hillforts, held in Prague in 2019. The main part of this article contains different examples of geophysical prospecting used in connection with archaeological research into the early medieval fortifications in Bohemia. Selected examples illustrate various conditions, combinations and possibilities of application of non-destructive geophysical methods. In several cases, the results of geophysical measurements can also be supplemented by the results of archaeological research or surveys.